2008
DOI: 10.4049/jimmunol.180.2.1098
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9 and CXCL10 Expression Are Critical for Control of Genital Herpes Simplex Virus Type 2 Infection through Mobilization of HSV-Specific CTL and NK Cells to the Nervous System

Abstract: CXCL9 and CXCL10 mediate the recruitment of T lymphocytes and NK cells known to be important in viral surveillance. The relevance of CXCL10 in comparison to CXCL9 in response to genital HSV-2 infection was determined using mice deficient in CXCL9 (CXCL9−/−) and deficient in CXCL10 (CXCL10−/−) along with wild-type (WT) C57BL/6 mice. An increased sensitivity to infection was found in CXCL10−/− mice in comparison to CXCL9−/− or WT mice as determined by detection of HSV-2 in the CNS at day 3 postinfection. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
135
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(154 citation statements)
references
References 55 publications
15
135
1
3
Order By: Relevance
“…CXCL10 deficiency was associated with a reduction in the mobilization of HSV-specific CD8 ϩ T cells into the brain as a result of dysregulation of CXCR3 signaling (31). CXCR3 Ϫ/Ϫ deficient mice are also reported to be susceptible to primary genital HSV-2 infection (61)(62)(63)(64). This susceptibility appeared to be associated with reduced cytotoxic function of CD8 ϩ T cells through impairment in expression of T-bet, perforin, and GzmB, as well as a reduction in the recruitment of pDC and impairment in CD80 expression on CD11c ϩ DC (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL10 deficiency was associated with a reduction in the mobilization of HSV-specific CD8 ϩ T cells into the brain as a result of dysregulation of CXCR3 signaling (31). CXCR3 Ϫ/Ϫ deficient mice are also reported to be susceptible to primary genital HSV-2 infection (61)(62)(63)(64). This susceptibility appeared to be associated with reduced cytotoxic function of CD8 ϩ T cells through impairment in expression of T-bet, perforin, and GzmB, as well as a reduction in the recruitment of pDC and impairment in CD80 expression on CD11c ϩ DC (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 Ϫ/Ϫ deficient mice are also reported to be susceptible to primary genital HSV-2 infection (61)(62)(63)(64). This susceptibility appeared to be associated with reduced cytotoxic function of CD8 ϩ T cells through impairment in expression of T-bet, perforin, and GzmB, as well as a reduction in the recruitment of pDC and impairment in CD80 expression on CD11c ϩ DC (61)(62)(63)(64). It is important to underline that, unlike the above studies that were done using mouse models of acute ocular and genital primary infections, our present studies used a mouse model of induced virus reactivation and recurrent herpes.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 is an inflammatory chemokine that mainly recruits activated T cells and NK cells to sites of infection and/or inflammation. Using mouse animal models, it has been shown that CXCL10 expression is significantly induced and plays a critical role in a variety of viral infections, including infection with measles virus (20), West Nile virus (21), lymphocytic choriomeningitis virus (42), murine hepatitis virus (19,22), and herpes simples virus (24,43). The primary function of CXCL10 in these viral diseases is to recruit effector cells to the sites of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the expression of CXCL9 was enhanced in HSV-2-infected mice (22), although the underlying mechanism remains to be addressed. CXCL9 levels in cervical mucus from HSV-2-negative (n = 41) and HSV-2-positive (n = 45) women were determined by ELISA.…”
Section: Cxcl9 Expression Is Elevated In the Cervical Mucus Of Hsv-2-mentioning
confidence: 99%
“…The four subfamilies of chemokines, CXC, CC, C, and CX3C, are characterized by the position of the N-terminal cysteine residues (20,21). Recent study indicates that chemokine CXCL9 can be induced in mice after HSV-2 infection and its expression is crucial for control of genital HSV-2 infection (22), although the mechanism remains to be addressed. The receptor for CXCL9, CXCR3, is functionally expressed on activated T and B cells, NK cells, and endothelial cells (23,24).…”
mentioning
confidence: 99%